The Influence of Customer Experience, Green Brand Image, and Green Product Quality on Green Customer Loyalty of Cosmetic Products - Candrawati Kartika Wijaya; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
The rapid growth of Indonesia’s cosmetics industry and the shift toward sustainable products make green customer loyalty, influenced by customer experience, brand image, and product quality, crucial for brands to remain competitive and build long-term sustainable relationships. This research investigates the impact of customer experience, green brand image, and green product quality on green customer loyalty of cosmetic products. The study involved a sample of 100 respondents. Data were collected using a non-probability sampling approach, with a questionnaire serving as the research instrument. The instrument test results confirmed that the data were both valid and reliable. According to the Classical Assumption Tests, the data are normally distributed, and the regression model is free from multicollinearity and heteroscedasticity issues. The study’s findings reveal that customer experience and green brand image positively and significantly affect green customer loyalty. In contrast, green product quality does not have significant effect on green customer loyalty. The findings imply that enhancing customer experience and strengthening green brand image are critical strategies for increasing green customer loyalty, while green product quality alone may not significantly influence loyalty for cosmetic products.